Ergonomic Considerations for Assembly and Disassembaly of Cng Tanks on a Vehicle - Loo, Woon Chek (2006)
The use of natural gas as an automotive fuel is expanding worldwide, particularly so with the increasing price of petrol and diesel. Natural gas vehicle (NGV) is a relatively new and rapidly evolving technology in Malaysia. As of 2005, there were more than 12,000 NGVs and 38 refuelling stations available in the country. However, the use of natural gas as a vehicle fuel creates challenges in vehicle design. The installation of compressed natural gas (CNG) cylinders into the vehicle requires an analysis of the space availability, mounting system, design to assembly, disassembly and maintenance, fasteners operations, visibility and labelling issues, therefore creating a new impact on the vehicle design. In this study, a petrol fuelled sedan type passenger car has been chosen as a case study by its conversion to bi-fbelled and mono-fuelled NGV. A total of four designs have been introduced: locating the CNG cylinders in the (i) luggage compartment and (ii) beneath the vehicle floor pan while retaining the original platform, also (iii) placing the cylinder under the backbone and (iv) rear platform by raising the floor. Ergonomics design guidelines and industrial NGV standards have played an important role in the design and design assessment. Many characteristics have been considered and studied to integrate the human into the system. These included equipment accessibility, workspace and operations, and physical accommodation. Virtual reality (VR), which enables the modelling of systems and components, was used for the simulation of assembly, disassembly, maintenance, reachability and visibility operations, and subsequently to evaluate and improve the designs. Concurrently, postural analyses were conducted using Rapid Upper Limb Assessment (RULA) technique. The virtual human contained within the VR software was used to perform the physical work, in an effort to reduce the risk of musculoskeletal disorder.